Modelling, Simulation And Speed Control Of Electric Vehicle - Saahari, Farahanizan (2020)
This thesis presents a simulation of an Electric Vehicle using MATLAB-Simulink software. The simulation is made by utilizing a 5 degree of fr dom (5-DOF) vehicle longitudinal model and a brushless direct current motor (BLDC) as the electric power train system In order to strengthen the study and to enhance the reliability of the results, validation was made to the 5-DOF vehicle model by adopting several vehicle behaviours and characteristics of Proton Iswara used by previous researchers. The validation tests performed in this study are acceleration then braking tests at 40 and 60 km/h, while the parameters are vehicle speed, tire longitudinal slip and wheel speed of the vehicle. By using the validated vehicle model and the electric power train system, a nonlinear-proportional integral controller was designed for the electric vehicle speed control. Several simulation tests were performed by employing the same reference speed as the vehicle validation and another reference speed proposed by Society of Automotive Engineer (SAE), namely the New European Driving Cycle (NEDC) and Worldwide Harmonised Light Vehicle Test Procedure (WLTP). Finally, the potential benefits of the proposed EV system together with the proposed speed control method were investigated. The speed control of the proposed system with an appropriate controller was demonstrated to be very promising.